Development tendencies of forms of organization of physical education in Europe in the Middle Ages - Dmitriy Solovey (Kharkiv State Academy of Physical Culture, 2015)
Purpose: identify and analyze trends in the development of forms of organization of physical education in Europe in the Middle Ages. Material and Methods: theoretical analysis and generalization of scientific literature, descriptive method, method of system analysis. Results: examined the main trends of formation and development of forms of organization of physical education in Europe in the Middle Ages. Conclusions: the main forms of physical education and forms of leisure activities, as well as factors that directly affect their development are revealed during researches. In particular, the content and organization of physical education were differentiated by belonging to a social level of society, and forms of physical education were stipulate by the characteristics of economic and cultural development, geographical conditions, traditions and lifestyle